Application and Evaluation of [Tc]-Labeled Peptide Nucleic Acid Targeting in Breast Cancer Imaging - Yaqun Jiang MD; Yongkang Gai PhD; Yu Long MD; Qingyao Liu PhD; Chunbao Liu MD, PhD; Yongxue Zhang MD; Xiaoli Lan MD, PhD (Molecular Imaging)
It has been reported that dysregulation of microRNA-155 expression and function is associated with tumorigenesis, growth, tumor subtypes, invasion, and poor survival rates. Peptide nucleic acid (PNA), an artificially synthesized nucleic acid mimic, has been applied for molecular diagnosis. In this study, a PNA sequence that undergoes complementary binding to miR-155 was labeled with 99m Tc to evaluate whether the tracer could visualize the expression of miR-155 in breast cancer. Both antisense PNA (anti-PNA, fully complementary bound to human mature miR-155 , referred to as “anti-PNA-155”) and mismatched PNA (referred to as “mis-PNA”) single strands containing 23-mer were synthesized. The relative expression of miR-155 in MCF-7 cells and tumors was higher than that in MDA-MB-231 cells and tumors. Single-photon emission computed tomography (SPECT) scan showed that radioactivity mainly accumulated in kidney. MCF-7 tumors, but not MDA-MB-231 tumors, were clearly visualized after [ 99m Tc]anti-PNA-155 injection. MCF-7 tumors were less visible when coinjected with 100-fold excess of anti-PNA-155 or injected with [ 99m Tc]mis-PNA, which suggested specific binding. Biodistribution study results were consistent with SPECT imaging. We successfully demonstrated that [ 99m Tc]anti-PNA-155 could visualize miR-155 expression in vivo, suggesting it may be a promising probe applied in breast cancer.